Content validity and reliability of test of gross motor development in Chilean children - Marcelo Cano-Cappellacci; Fernanda Aleitte Leyton; Joshua Durán Carreño (Universidade de São Paulo, 2015)
ABSTRACT OBJECTIVE To validate a Spanish version of the Test of Gross Motor Development (TGMD-2) for the Chilean population. METHODS Descriptive, transversal, non-experimental validity and reliability study. Four translators, three experts and 92 Chilean children, from five to 10 years, students from a primary school in Santiago, Chile, have participated. The Committee of Experts has carried out translation, back-translation and revision processes to determine the translinguistic equivalence and content validity of the test, using the content validity index in 2013. In addition, a pilot implementation was achieved to determine test reliability in Spanish, by using the intraclass correlation coefficient and Bland-Altman method. We evaluated whether the results presented significant differences by replacing the bat with a racket, using T-test. RESULTS We obtained a content validity index higher than 0.80 for language clarity and relevance of the TGMD-2 for children. There were significant differences in the object control subtest when comparing the results with bat and racket. The intraclass correlation coefficient for reliability inter-rater, intra-rater and test-retest reliability was greater than 0.80 in all cases. CONCLUSIONS The TGMD-2 has appropriate content validity to be applied in the Chilean population. The reliability of this test is within the appropriate parameters and its use could be recommended in this population after the establishment of normative data, setting a further precedent for the validation in other Latin American countries.